CAI YONG'S 蔡邕 READING OF THE ODES, AS SEEN FROM HIS QINCAO 琴操 AND HIS "QINGYI FU" 青衣賦. (September 2022) - Schaab-Hanke, Dorothee
Abstract: Cai Yong 蔡邕 (132–192) was one of the most erudite scholars of the Eastern Han. A major project of his was the so-called "Stone Classics of the Xiping era" (Xiping Shijing 熹平石經) project first commissioned by Emperor Ling in 175 c.e ., for which Cai Yong wrote the texts of the court-sanctioned Classics in his own calligraphy. For the text of one of these Classics, the Odes ( Shi 詩), he is known to have used the so-called Lu 魯 version, which was the dominant interpretative line for the Odes classic in his time. However, the question of whether Cai Yong's literary writings also evince a preference for the Lu reading of the Odes has not yet received much scholarly consideration. In my study, the Qincao 琴操, a collection of anecdotes and song texts relating to pieces played to the accompaniment of the zither qin, a work that may also be assigned to Cai Yong but has also mostly been neglected so far, will be analyzed in relation to the Lu interpretive line, as will the "Qingyi fu" 青衣賦 (Rhapsody on a Grisette), one of Cai Yong's rhapsodies.